Pengaruh Penerapan Model PBL Berbantuan Media Video Terhadap Hasil Belajar Tema 8 Subtema 2 - Nadhira Nur Hidayati; Yuli Mulyawati; Santa Santa (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This study aims to determine the effect of the PBL model on learning outcomes of Theme 8 Subtheme 2 at Margajaya 1 Bogor City Class IV State Elementary School, especially in Thematic learning. This type of research is a type of quantitative research with a quasi-experimental approach and a nonequivalent control group design. The population in this study were all fourth grade students of SD Negeri Margajaya 1 in the 2021/2022 school year, totaling 58 students who were also the research sample. Based on data analysis, there is a difference between the average pretest and posttest learning outcomes. Based on the calculation of t count (5.89887) > t table (2.00324), Ho is rejected. In addition, the completeness of learning outcomes in the experimental class was 96.5%, while the completeness of learning outcomes in the control class was 86.2%. So it can be stated that the effect of applying the PBL model has an influence on the learning outcomes of Theme 8 Subtheme 2 of class IV SDN Margajaya 1 Bogor City Even Semester 2021/2022 academic year.